Management of Low-Grade Gliomas – Extent of Resection Matters But Not All Tumours Are Amenable to Surgery. (1st October 2022) - Sokratous, Giannis; Sokratous, Jill; Bakhsh, Ali; Brodbelt, Andrew; Chavredakis, Emmanuel; Lawson, David; Farah, Jibril; Shenoy, Aditya; May, Chloe; Jenkinson, Michael; Mehta, Shaveta
Abstract: AIMS: To present and review our experience in the management of low-grade gliomas. METHOD: Retrospective case note review of all patients with WHO grade 2 glioma from 2011 to 2018 (based on WHO criteria at time of diagnosis). Data collected on demographics, presentation, location, initial management, histology, treatment, progression free (PFS) and overall survival (OS). RESULTS: 130 eligible patients. Median follow 4.6 years (up to 10.5). Median age 40 years (range: 18-83). There were 70 (53.8%) astrocytomas, 44 (33.8%) oligodenrogliomas, 16 (12.3%) oligoastrocytomas. 66%(n=86) presented with seizures, 10.7%(n=14) with sensory symptoms, 8.5%(n=11) with speech disturbance, 5.3%(n=4) with motor symptoms and 12.3%(n=16) were identified incidentally. 50.1%(n=65) were frontal, 27.7%(n=36) temporal and 9.2%(n=12) parietal. 1st line treatment was resection in 70.7%(n=92), biopsy in 23.8%(n=31) and observation in 4.6%(n=6). 15.4%(n=20) received adjuvant radiotherapy alone and 6.1%(n=8) received adjuvant radiotherapy followed by chemotherapy . At first recurrence, 31.6%(n=12) received further surgery and 95%(n=38) received radiotherapy and/or chemotherapy . Median PFS from 1st line treatment 66, 44 and 33 months for gross total resection (GRT), subtotal resection (STR), and biopsy respectively. Overall survival was 95.1%, 79.3% and 69.% for GTR, STR and biopsy respectively. CONCLUSION: Management of low-grade gliomas remains challenging. Extent of resection impacts prognosis but not all patients have gliomas amenable to surgery. The effects of chemoradiotherapy will be presented in future meetings as this is an ongoing project.